Passive acoustic monitoring for estimating human-wildlife conflicts: The case of bee-eaters and apiculture. (September 2022) - Bota, Gerard; Traba, Juan; Sardà-Palomera, Francesc; Giralt, David; Pérez-Granados, Cristian
Highlights: Passive acoustic monitoring (PAM) can be used for monitoring human-wildlife conflicts. One of such conflicts is that occurring between apiarists and bee-eaters. Vocal Activity Rate (VAR) is an useful indicator of bee-eater pressure at beehives. Bee-eater pressure was higher at early morning and evening and during bird migration. Honeybees activity was negatively associated with VAR but varied between hours. Abstract: In human-wildlife conflicts, it is crucial to develop accurate protocols for the reliable verification of the causative species and its relationship with potential damage claims. One of such conflicts is that occurring between apiarists and bee-eaters. In this work, we aim to assess the utility of passive acoustic monitoring (PAM) as an efficient methodology to measure European bee-eater ( Merops apiaster ) predation pressure at beehives and its impact on honeybees foraging activity. Using Autonomous Recording Units (ARUs) in apiaries, coupled to automated recognition methods for bee-eater calls identification, we found a positive relationship between Vocal Activity Rate (VAR) index and number of bee-eaters hunting attempts on honeybees. We also found that VAR varied over time, showing a lower predation pressure during midday hours and higher during the post-breeding migratory period. Honeybees flying activity was negatively associated with VAR and this relationship was conditioned by the hour of the day. Our study offers a new application of PAM and acoustic derived indices for the evaluation of potential damages caused by wildlife. We focused on the interaction between honeybees and the European bee-eater, but we expect PAM might be useful also to remotely monitor impacts to human activities produced by other vocally active species.